Management and outcome of newly diagnosed wilms{u2019} tumor at National Cancer Institute Cairo University and Children Cancer Hospital, Egypt - Moatasem Mohamed Hatem Elayadi; Alaa Abdelhamid Younes; Emad Nabil Ebeid; Mohamed Saad Zaghloul (Cairo : Moatasem Mohamed Hatem Elayadi, 2014)
Our study aimed at evaluating the demographics, disease characteristics and treatment outcome for unilateral WT patients treated at National Cancer Institute, Cairo University and Children Cancer Hospital, Egypt (57357). This cohort study included 135 eligible patients with newly diagnosed nephroblastoma during the period from January 2010 to December 2011. The median follow up period was 29.3 months (range 0.3 to 46.6 months). Our results concluded that outcome of unilateral WT is generally good for early stages and comparable to results from other groups. Metastatic state at presentation was associated with significant reduction in OS and EFS rates
Thesis (Ph.D.) - Cairo University - National Cancer Institute - Department of Pediatric Oncology
Issued also as CD
Keywords: Paediatric Oncology; Renal Tumors; Survival Rates